CONCEPTUAL LIMITATIONS IN EPIDEMIOLOGY IN THE CLASSIFICATION OF MALE SEXUAL BEHAVIOR IN THE CONTEXT OF THE HIV EPIDEMIC IN MEXICO (Andamios, Revista de Investigación Social, 2008)
The role of epidemiology in the study of Human Immunodeficiency Virus (HIV) and its spread among human populations has been outstanding. The epidemiological theory about “multi-factorial etiology” has allowed the identification of the main “risk factors” of HIV infection, particularly those related to sex practices. Nevertheless, that theory has epistemological limitations to study the social and cultural elements related to sexual behavior in the context of HIV. As a result, we propose to improve the epidemiological theory where the study of sexual behavior is concerned by including gender concepts like sexual identity and sexual role, because these concepts are close to the main objective of sexual behavior study in epidemiology, which is sexual practices.
Keywords: Epidemiology; risk analysis; HIV infection; sexual practices; gender role; sexual identity